NLST ACRIN Biomarker Repository Originating from the Contemporary Screening for the Detection of Lung Cancer Trial (NLST, ACRIN 6654):Design, Intent, and Availability of Specimens for Validation of Lung Cancer Biomarkers - Patz, Edward F. (2010)
Lung cancer continues to be a major public health problem, and more patients die from this disease than any other cancer. The vast majority of patients present with advanced stage disease when therapeutic options are limited and the overall 5 year survival rate remains approximately 15%. Screening with low dose helical computed tomography (CT)has been suggested for early detection, although the effect on mortality is currently under investigation. As part of the National Lung Cancer Screening Trial, a specimen biorepository including blood, sputum, and urine were collected serially for the primary purpose of validating early detection lung cancer biomarkers. In addition tumor samples have been obtained from patients diagnosed with lung cancer to be included in a tissue microarray. This commentary describes the rationale, composition, intent, and availability of specimen in the biorepository.